UV‐B photoreceptor UVR8 interacts with MYB73/MYB77 to regulate auxin responses and lateral root development - Yang, Yu (EMBO J, 2019)
The UV‐B photoreceptor UVR8 mediates multiple UV‐B responses in plants, but the function of UVR8 in regulating root development has not previously been investigated. Here, we show that UV‐B light inhibits Arabidopsis lateral root growth in a UVR8‐dependent manner. Monomeric UVR8 inhibits auxin responses in a tissue‐autonomous manner and thereby regulates lateral root growth. Genome‐wide gene expression analysis demonstrated that auxin and UV‐B irradiation antagonistically regulate auxin‐regulated gene expression. We further show that UVR8 physically interacts with MYB73/MYB77 (MYB DOMAIN PROTEIN 73/77) in a UV‐B‐dependent manner. UVR8 inhibits lateral root development via regulation of MYB73/MYB77. When activated by UV‐B light, UVR8 localizes to the nucleus and inhibits the DNA‐binding activities of MYB73/MYB77 and directly represses the transcription of their target auxin‐responsive genes. Our results demonstrate that UV‐B light and UVR8 are critical for both shoot morphogenesis and root development. The UV‐B‐dependent interaction of UVR8 and MYB73/MYB77 serves as an important module that integrates light and auxin signaling and represents a new UVR8 signaling mechanism in plants.